(3JMdjd hJbjje GdCSge hGdSfOGJ (B/s - (3GdMfGhj, eMeO GdUGdMs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3CSGSjGJ GdGSJKeGQ aj ChQGb GdeGdjI,TQGA hHjY GdGhQGb GdeGdjI,GdJMdjd GdeGdj ddGSge,caGAI Shb GdGhQGb GdeGdjI,GdJMdjd Gdafj ddGSge,feGPL Jbjje GdGSge GdYGOjI , JMdjd GdSfOGJ,CSGSjGJ eMaXI GdGhQGb GdeGdjI hJbjje COGFgG,Mbhb GdGNJjGQ ,YbhO GdeHGOI hGdYbhO GdeSJbHdjI(B.s
(3GdeQGLY U(B.443s
Keywords: (3GdCSges; (3GdHhQUIs; (3GdSfOGJs